Contemporary Chinese newspaper discourse on translation: A mixed-methods approach to the People’s Daily (1949–2023) - Xinyu Shi; Libo Huang (PLoS ONE, 2026)
Newspaper discourse on translation forms a particular discourse that uses newspapers as a medium to discuss the products, processes, and functions of translation. It can reflect how a society perceives translation as a general phenomenon in a certain period. Adopting a mixed-methods approach to the contemporary Chinese newspaper discourse on translation, this study examines the perceived roles of translation in the People’s Daily between 1949 and 2023. It identifies main translation-related terms in the discourse through frequency analysis, traces the developmental trajectories of those terms through time series analysis, and investigates the discourse focuses in different periods based on corpus-assisted discourse analysis. The findings show that there are diachronic changes in the perceived roles of translation, and that such changes are closely related to the broader sociopolitical, economic, and cultural context of China. This study has some implications for expanding interdisciplinary approaches to translation studies and helps explore the interactive relationships between translation, discourse, and social changes.